Some functional differential equations with both retarded and advanced arguments - Ilea, Veronica Ana (Rev. Anal. Numér. Théor. Approx., 2009)
In this paper we shall study a functional differential equation of mixed type. This equation is a generalization of some equations from medicine. Related to this equation we study the existence of the solution by contraction's principle and Schauder's fixed point theorem.